Teaching extent and military service improve undergraduate self-assessed knowledge in disaster medicine: An online survey study among Swedish medical and nursing students - Robinson, Yohan; Ragazzoni, Luca; Della Corte, Francesco; von Schreeb, Johan (Frontiers in Public Health, 2023)
Background The purpose of this study was to identify the possible needs for undergraduate disaster medicine education in Sweden and to make informed recommendations for the implementation of disaster medicine content in medical and nursing schools in Sweden. Methods An online survey was distributed to undergraduate medical and nursing students through the directors of all medical and nursing programs at Swedish universities. The survey contained demographic questions, as well as questions about the amount of disaster medical education and previous experience with rescue, police, or military services. The final survey page contained self-assessments of disaster medical knowledge. Comparative statistics were applied between nursing and medical students, those with previous military service, and those without, as well as between universities. Results A total of 500 medical and 408 nursing students participated in this study. A median of 2 h of disaster medicine education was provided to senior medical students and 4 h was provided to senior nursing students. Senior medical students scored their disaster medical knowledge lower than nursing students (t-test, p < 0.001). A proportion of 1% had served in rescue services or police, and 7% of the participants had a history of military service, of which 67% served in a medical role. Those who had served in rescue services, police, or the armed forces had a higher self-assessed disaster medical knowledge base than those who had not (p < 0.007 and p < 0.001, respectively). Conclusion Most medical and nursing students in this study rated their disaster medical knowledge as insufficient. The correlation between the amount of disaster medical education and self-assessed disaster medical knowledge should influence and help direct Swedish educational policies.